Cancer development, chemoresistance, epithelial to mesenchymal transition and stem cells: A snapshot of IL-6 mediated involvement. Issue 1 (28th May 2016) - Bharti, Rashmi; Dey, Goutam; Mandal, Mahitosh
Highlights: IL-6 is a critical cytokine involved in malignant transformation and progression. IL-6 regulates cancer stem cell and mesenchymal stem cell formation. IL-6 induces epithelial to mesenchymal transition (EMT) in cancer. Overexpression of IL-6 is the contributing factor for chemoresistance. Abstract: Interleukin-6 (IL-6) is a cytokine present in tumor microenvironment. Elevated level of IL-6 is associated with cancer cell proliferation, angiogenesis and metastasis through fueling STAT3, MAPK and Akt signaling. It promotes epithelial to mesenchymal transition (EMT) through altered expression of N-cadherin, vimentin, snail, twist and E-cadherin leading to cancer metastasis. IL-6 boosts mammosphere formation, self-renewal of stem cells, stemness properties of cancer cells and recruitment of mesenchymal stem cells. IL-6 is also a contributing factor for multidrug resistance in cancer due to gp130/MAPK/STAT3 mediated activation of transcription factors C/EBPβ/δ, overexpression of p-glycoprotein, EMT transition and expansion of stem cells. The in-depth investigation of IL-6 mediated cellular effects and its signaling pathway can provide the new window for future research and clinical development of IL-6 targeted therapy in cancer. Thus, an overview is delivered in this review deciphering the emerging aspect of the predominant influence of IL-6 in malignant transformation, EMT, cancer-associated stem cells and chemoresistance .